Electromagnetic Levitation Control for Bending Flexible Steel Plate: Experimental Consideration on Disturbance Cancellation Control - Kazuki Ogawa; Makoto Tada; Takayoshi Narita; Hideaki Kato (Actuators, 2018)
When an ultrathin and flexible steel plate is to be levitated, levitation control becomes difficult because the ultrathin steel plate undergoes increased flexure. We herein propose a levitation method for an ultrathin steel plate that is bent to an extent that does not induce plastic deformation. In this study, to investigate the levitation stability of an ultrathin steel plate, we applied disturbance cancellation control in the bending levitation system. The object of electromagnetic levitation was a rectangular zinc-coated ultrathin steel plate (SS400) of length 800 mm, 600 mm, and thickness 0.19 mm. The vibrator was attached below the three frames, in which the electromagnet unit was installed so that the frames could be vibrated up and down. We conducted experiments on the levitation performance when the electromagnet was displaced by the frame vibration in the bending levitation system. The results showed that a stable levitation can be achieved even with an input of external disturbance when levitating at the optimum bending angle.